Attribution of Ghrelin to Cancer; Attempts to Unravel an Apparent Controversy - Soleyman-Jahi, Saeed; Sadeghi, Fatemeh; Pastaki Khoshbin, Amin; Khani, Leila; Roosta, Venus; Zendehdel, Kazem (Frontiers in Oncology, 2019)
Ghrelin is an endogenous peptide hormone mainly produced in stomach. It has been known to regulate energy homeostasis, stimulate secretion of growth hormone, and mediate many other physiologic effects. Various effects attributed to ghrelin provides it with potential contributions to many aspects of cancer development and progression. Accordingly, large body of evidence has emerged about attributions of ghrelin to many types of cancer in scales of cell-line, animal, and human studies. However, existing data are controversial. This controversy occurs in two main domains: one is the controversial results in local effects of ghrelin on different types of human cancer cell-lines; the second is the apparent controversy in results of in-vitro and clinical studies that investigated ghrelin attributions to one type of cancer. These inconsistencies have hampered the indications to consider ghrelin as a potential tumor biomarker or therapeutic agent in cancer patients. Previous studies have reviewed different parts of current literature about ghrelin-cancer relationship. Although they have spotted these controversial results in various ways, no specific recommendations have been given to address it. In this study, we comprehensively reviewed in-vitro, in-vivo, and clinical studies and attempted to use following approaches to unravel inconsistencies detected: a) to distinguish local and systemic effects of ghrelin in interpreting its summary clinical role in case of each cancer; b) scrutinizing factors that regulate local effects of ghrelin and could justify different effects of ghrelin on different cancer cell-lines. These approaches could have notable implications for future in-vitro and clinical studies.